2020
DOI: 10.3390/cancers12040824
|View full text |Cite
|
Sign up to set email alerts
|

Chromosome Instability; Implications in Cancer Development, Progression, and Clinical Outcomes

Abstract: Chromosome instability (CIN) refers to an ongoing rate of chromosomal changes and is a driver of genetic, cell-to-cell heterogeneity. It is an aberrant phenotype that is intimately associated with cancer development and progression. The presence, extent, and level of CIN has tremendous implications for the clinical management and outcomes of those living with cancer. Despite its relevance in cancer, there is still extensive misuse of the term CIN, and this has adversely impacted our ability to identify and cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
56
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(58 citation statements)
references
References 158 publications
(208 reference statements)
0
56
0
2
Order By: Relevance
“…It should be noted that many current therapeutic strategies are based on the rationale of inducing excessive levels of CIN that are not compatible with viability [ 74 , 75 , 76 , 77 , 78 ]. Despite the effective killing, the emergence of drug resistance is common.…”
Section: Conclusion and Future Perspectivementioning
confidence: 99%
“…It should be noted that many current therapeutic strategies are based on the rationale of inducing excessive levels of CIN that are not compatible with viability [ 74 , 75 , 76 , 77 , 78 ]. Despite the effective killing, the emergence of drug resistance is common.…”
Section: Conclusion and Future Perspectivementioning
confidence: 99%
“…In addition to whole chromosomal instability and heterogeneity, other genetic modifications may influence the development of tumors and metastasis. These include genetic amplifications, translocations, or DNA repair deficiencies [ 103 , 104 , 105 ]. The first two involve structural changes in specific genes or chromosomal regions (i.e., BCR/ABL fusion in chronic myelogenous leukemia [ 106 ]) while DNA repair deficiencies can affect multiple genes in the cell [ 104 ].…”
Section: Genetic and Chromosome Instabilitymentioning
confidence: 99%
“…The first two involve structural changes in specific genes or chromosomal regions (i.e., BCR/ABL fusion in chronic myelogenous leukemia [ 106 ]) while DNA repair deficiencies can affect multiple genes in the cell [ 104 ]. DNA repair deficiencies can lead to gene sequences modifications, translation error of proteins, activation of oncogenes or inactivation of tumor-suppressor genes [ 104 , 105 ], and consequently tumor evolution and metastasis [ 103 , 104 ].…”
Section: Genetic and Chromosome Instabilitymentioning
confidence: 99%
“…A systematic review and meta-analysis associated with human embryos chromosome in 2011 reported that 73% of all human embryos contain aneuploid cells 2,3 . Chromosomal instability (CIN) plays a key role in aneuploidy and tumorigenesis 4 . In this context, spindle assembly checkpoint (SAC) is crucial to ensure delity of chromosome segregation during mitosis.…”
Section: Prefacementioning
confidence: 99%